Trapezium Fracture: An Overview of Percutaneous Fixation - Vetri R. Nallathambi; V. Raviraman (New Advances in Medicine and Medical Science Vol. 6, 2023)
Trapezoidal fractures occur due to high energy trauma and is usually associated with other carpal fractures. Isolated Trapezoidal fracture is a rare diagnosis which can lead to long term symptoms if missed. Usual pattern is a vertical fracture type. Displaced Trapezoidal fractures can be treated by either open or closed technique using k-wire or Herbert screw fixation. Good functional outcome has been reported after surgical fixation in spite of radiological signs of arthritis. High suspicion and clinical knowledge is necessary to avoid missing these injuries and in preventing complications.